"Same stuff different day:" A mixed-method study of support seeking on Facebook. (December 2015) - Blight, Michael G.; Jagiello, Kristy; Ruppel, Erin K.
Highlights: Perceived supportiveness was positively associated with offline support. Facebook intensity nor total likes were associated with perceived supportiveness. Support seeking updates: positive/negative, mixed, requests, quotes, and vague. Most supportive comments came from acquaintances rather than close others. Top supportive comments provided emotional, informational, or tangible support. Abstract: Facebook allows users to seek support from close others and acquaintances. This study examined features of support-seeking Facebook status updates and factors related to perceived supportiveness of responses. College students using Facebook to seek support ( N  = 149) provided copies of their support-seeking status updates and descriptions of the most supportive comment received on the status. Participants responded to survey items including offline social support, Facebook intensity, and number of "likes" the status received. Participants sought support using positive, negative, mixed, vague comments, or quotations not explicitly statuses. Participants identified emotional, informational, or tangible support from close others (68.03%) rather than acquaintances (31.97%). Perceived supportiveness of responses was positively associated with offline social support but was not associated with Facebook intensity or number of "likes."